PRIMA 2018 : Principles and Practice of Multi-Agent Systems : 21st International Conference, Tokyo, Japan, October 29-November 2, 2018, Proceedings /: Principles and Practice of Multi-Agent Systems : 21st International Conference, Tokyo, Japan, October 29-November 2, 2018, Proceedings. (2018) - Unknown
No abstract available